Computational study of internal aerodynamic flow in a transonic diffuser - Balajee Ramakrishnananda (2009)
This work is concerned with the computational study of aerodynamic flow through the blade passages of a transonic centrifugal diffuser. Euler and Reynolds-averaged Navier-Stokes equations are solved numerically by an explicit finite volume method utilizing a multi-stage time stepping scheme enhanced with several conver-gence acceleration schemes such as local time-stepping, implicit residual smoothing and multigrid strategies to compute steady state solutions for flows through a high performance transonic vaned centrifugal diffuser. An algebraic turbulence model is employed for modelling turbulent flows